Metaxenia in apples cv. ’Rewena’, ’Relinda’, ’Baujade’ as influenced by scab resistant pollinizers - Bodor, P.; Gaál, M.; Tóth, M. (International Journal of Horticultural Science, 2008)
Fruit quality of cross pollinated apples (Malus x domestica) influenced by the metaxenic pollen effect of the pollinizer was observed in Hungary. Flowers of three resistant cultivars (`Baujade’, `Rewena’) were hand pollinated with other resistant apple cultivars. Fruits were harvested on 25 September, 2005. Fruit quality was investigated in the laboratory of the Department of Pomology; Corvinus University of Budapest. Not only size and morphological parameters (diameter, height, stem length), but also refraction and acidic content of the fruits were measured. According to the statistical analysis significant differences were determined on fruits among the groups as an effect of the pollen provider. In consideration of size parameters (diameter, height, weight) of `Rewena’ fruits pollination partner ’Freedom’ and ’Prima’ caused outstanding results but `Florina’ caused flatter fruits. Pollen of `Florina’ and `Freedor-,’ caused a higher percent refraction in the fruits of `Rewena’. In the case of `Baujade’ fruits `Reglindis’ — among cultivars we used as pollinizer — caused the biggest fruits medium flesh firmness and harmonic inner content values. `Rajka’ caused on one hand smaller fruits and on the other hand higher flesh firmness and inner content values in the case of `Relinda’ fruits. According to our data measured pollinizers varied the stem length as well.